Productivity and soil fertility of wheat (Triticum aestivum L.) as influenced by phosphorus, zinc and iron nutrition - JAT, R. C.; SHARMA, YOGESH; KUMAWAT, AMIT; PAREEK, N. K. (Journal of Soil and Water Conservation, 2020)
Abstract